2001
DOI: 10.1159/000048868
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase 2 Expression in Chronic Pancreatitis: Correlation with Stage of the Disease and Diabetes mellitus

Abstract: Background: Fibrotic replacement of the exocrine pancreatic parenchyma and infiltration of inflammatory cells are the main characteristics of chronic pancreatitis (CP). Inflammation involves prostaglandin production in numerous inflammatory and noninflammatory cells, and cyclooxygenase 2 (COX-2) is the dominant regulator of prostaglandin synthesis. Aims: In the present study, we analyzed the expression of COX-2, the key enzyme for prostaglandin synthesis in pancreatic tissues, and evaluated its relation to exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…40) Moreover, chronic renal dysfunction in human disease, such as diabetes mellitus and aging, increase COX-2 protein expression. 43,44) In our study, GSPs inhibited high glucose-induced COX-2 protein overexpression, but monomer GSPs showed a weaker inhibitory effect than other GSPs (oligomer, polymer, and oligonol) (Fig. 4).…”
Section: Discussionmentioning
confidence: 50%
“…40) Moreover, chronic renal dysfunction in human disease, such as diabetes mellitus and aging, increase COX-2 protein expression. 43,44) In our study, GSPs inhibited high glucose-induced COX-2 protein overexpression, but monomer GSPs showed a weaker inhibitory effect than other GSPs (oligomer, polymer, and oligonol) (Fig. 4).…”
Section: Discussionmentioning
confidence: 50%
“…COX-2 is directly related to the severity of pancreatic tissue inflammation, and its main function is to catalyze the conversion of arachidonic acid products into prostaglandin [8,37,42]. Equally to this work, Schlosser et al [8] also found an increased expression of COX-2 in patients with ACP.…”
Section: Discussionmentioning
confidence: 60%
“…Thirty-one patients with CP were categorized into three groups according to the preoperative glucose tolerance test (Koliopanos et al 2001): group A consisted of 14 patients with no history of disturbance of glucose metabolism and a normal preoperative glucose tolerance test; group B comprised 9 patients with no history of disturbance of glucose metabolism, but latent diabetes mellitus in the preoperative glucose tolerance test; and group C was made up of 8 patients with manifest diabetes mellitus (6 cases of insulin-dependent diabetes mellitus and 2 cases on oral hypoglycemic therapy).…”
Section: Clinical Endocrine Statusmentioning
confidence: 99%